Integrated Analysis of the Transcriptome and Metabolome Reveals Genes Involved in Terpenoid and Flavonoid Biosynthesis in the Loblolly Pine (Pinus taeda L.) - Mao, Jipeng; Huang, Linwang; Chen, Manyu; Zeng, Weishan; Feng, Zhiheng; Huang, Shaowei; Liu, Tianyi (Frontiers in Plant Science, 2021)
Loblolly pine (Pinus taeda L.) is an afforestation with substantial economic and ecological value. Many metabolites with pharmacological activities are present in the tissues of P. taeda. However, the biosynthesis regulatory mechanisms of these metabolites are poorly understood. In the present study, transcriptome and metabolome analyses were performed on five tissues of P. taeda. A total of 40.4 million clean reads were obtained and assembled into 108,663 unigenes. These were compared with five databases, revealing 39,576 annotated unigenes. A total of 13,491 differentially expressed genes (DEGs) were observed in 10 comparison groups. Of these, 487 unigenes exhibited significantly different expression in specific tissues of P. taeda. The DEGs were explored using Gene Ontology and Kyoto Encyclopedia of Genes and Genomes metabolic pathway analysis. We identified 343 and 173 candidate unigenes related to the biosynthesis of terpenoids and flavonoids, respectively. These included 62 R2R3-MYB, 30 MYB, 15 WRKY, seven bHLH, seven ERF, six ZIP, five AP2, and one WD40 genes that act as regulators in flavonoid and/or terpenoid biosynthesis. Additionally, metabolomics analysis detected 528 metabolites, among which 168 were flavonoids. A total of 493 differentially accumulated metabolites (DAMs) were obtained in 10 comparison groups. The 3,7-Di-O-methylquercetin was differentially accumulated in all comparison groups. The combined transcriptome and metabolome analyses revealed 219 DEGs that were significantly correlated with 45 DAMs. Our study provides valuable genomic and metabolome information for understanding P. taeda at the molecular level, providing a foundation for the further development of P. taeda-related pharmaceutical industry.